Perder y ganar : historia de una conversación - Newman, John Henry, 1801-1890; García Ruiz, Víctor; Newman, John Henry, 1801-1890. (Madrid : Encuentro, 2009)
This is Newman's first novel: the story of a young man's search for faith and certainty amid the competing loyalties of early Victorian Oxford. It is remarkable as a vivid period piece and fascinating for what it reveals about Newman himself. Light-hearted and genial in spirit, and rich in comic scenes and characters, the novel challenged the easygoing values of the time, and it can still stir readers today to confront their own assumptions and priorities. It is, above all, a moving human story.
Online resource; title from PDF title page (Digitalia, viewed August 29, 2016)
Keywords: University of Oxford -- Students -- Fiction; Anglican Communion -- England -- Fiction; Conversion -- Catholic Church -- Fiction; Faith -- Fiction; Oxford (England) -- Fiction; Great Britain -- History -- 19th century -- Fiction; Electronic books